Determination of the health economic factors demanded by the Malaysian hajj pilgrims in Makkah in 2013 - Nor, Nor Radhiah Mat (2018)
Desire among Muslim around the world to perform Hajj is tremendously high as it is the fifth pillar in Islam and compulsory for Muslim who is mentally, physically and financially capable. Hajj is an annual Muslim pilgrimage to Makkah that involved 2.5 million pilgrims from all around the world. It caused huge congestion that could lead to potential diseases outcomes and numerous problems during its performance. The objectives of this study are generally; to study the demand for healthcare services among the Malaysian Hajj pilgrims in Makkah in 2013 and specifically; (1) to determine the type of health problems faced by the Malaysian pilgrims during Hajj, (2) to identify healthcare services demand by the Malaysian pilgrims in Makkah during Hajj, and (3) to determine the health economics factors associated to demand for health provision among Malaysian pilgrims during Hajj. A cross-sectional study was conducted that involved 379 Malaysian pilgrims in 2013/1434H. The survey was conducted after the pilgrims completed their Hajj ritual. Earlier, a qualitative study that was a Focus Group Discussion (FGD) was conducted as a baseline data collection for questionnaire construction. Six groups of participants were involved, where 36 participants were selected based on inclusion and exclusion criteria. A total of 400 sets of questionnaires were distributed at Abraj Janadriyah Hotel, which was occupied by more than 3000 Malaysian pilgrims. The response rate for this survey was 93%. Male respondents were constituted of 49.6% and female respondents were 50.4% with the mean age 52 years old. The underlying disease among Malaysian pilgrims during Hajj was respiratory disease (77.5%). Various problems were encountered during Hajj, where healthcare services (52%) were substantially highlighted by the pilgrims, followed by the public services (15%), Hajj management (12%), Hajj activity (8%), hygiene issues (7%), and food quality (6%). The health personnel (36.1%) and quality medication (34.7%) are among the important healthcare services demanded by the Malaysian pilgrims in Makkah. The health economic factors related to facilities during the ritual, such as public services (bus, or/and car), healthcare services and the food management were found significantly (p<0.05) associated with the confronted problems and type of diseases (communicable and non-communicable diseases) commonly affected population within the congestion. In conclusion, this research provides a fundamental input to be reference for the health care providers, and the Hajj management authority to improve the quality and improve efficiency of Hajj management in for Malaysian pilgrims in year ahead.